Six Months vs. 12 Months of Adjuvant Trastuzumab Among Women With HER2-Positive Early-Stage Breast Cancer: A Meta-Analysis of Randomized Controlled Trials - Deng, Huan; Du, Xianghui; Wang, Li; Chen, Ming (Frontiers in Oncology, 2020)
Abstract Purpose: Both 12-months and 6-months of trastuzumab in combination with chemotherapy are effective for HER2+ early-stage breast cancer. This meta-analysis was performed to assess the effectiveness and toxicity of the two durations. Methods and Materials: We acquired relevant randomized controlled trials (RCTs) from PubMed, the Cochrane Library, ScienceDirect, EMBASE, Ovid MEDLINE, Web of Science, Scopus, and Google Scholar. Our endpoints included disease-free survival (DFS), overall survival (OS), number of recurrences, mortality and early stopping of trastuzumab, and adverse events (AEs). Results: We included five good-quality studies. Both durations of trastuzumab were effective among women with HER2+ early-stage breast cancer, but 12-months of trastuzumab appeared to have better DFS (hazard ratio (HR) = 1.10, 95% confidence interval [CI]: 0.99-1.23, P=0.09) and better OS than 6-months of trastuzumab (HR=1.14, 95% CI: 0.99-1.32, P=0.07). However, the 12-months group had more AEs, especially cardiac events (risk ratio (RR) = 0.66, 95% CI: 0.56-0.77, P< 0.00001). In our sub-analyses, the 12-months duration had better DFS among patients using trastuzumab concurrently than the 6-months duration (HR=1.23, 95% CI: 1.06-1.44, P=0.006). Additionally, the 12-months duration had superior OS in women with ER-negative breast cancer (HR=1.51, 95% CI: 1.10-2.08, P=0.01) and patients treated with trastuzumab concurrently than the 6-months duration (HR=1.61, 95% CI: 1.13-2.29, P=0.008). Conclusions: 12-months was the standard duration of adjuvant trastuzumab among patients with HER2+ early-stage breast cancer, with a tendency toward superior survival. However, patients in the 12-months group had more significant cardiac toxicity than those in the 6-months group.